Obstructive sleep apnea syndrome in children with cerebral palsy in Brazil: a multicenter study - Bruno Leonardo Scofano Dias; Fernanda Marinho de Lima; Daniela Fava; Fernanda Jordão Pinto Marques; Frederico José de Carvalho Godinho; Alessandra Lemos de Carvalho; Sara Virgínia Paiva Santos; Fernanda de Lourdes da Cunha Pinto; Danielle Bruno Jardim; Wilerson Marques Bessa (Jornal de Pediatria)
Objectives: To evaluate the prevalence of high risk for obstructive sleep apnea syndrome (HR-OSAS) in Brazilian children with cerebral palsy (CP) using the Pediatric Obstructive Sleep Apnea Screening Tool (PosaST) and to analyze its association with demographic, clinical and functional (Gross Motor Function Classification System [GMFCS]) variables. Methods: Multicenter, cross-sectional, exploratory study. Results: There were 312 children (median age 6.0 years, IQR 5.0–8.0) included. The prevalence of HR-OSAS in GMFCS I-V was 9.0 %. The prevalence of HR-OSAS in GMFCS V (14.7 %) was significantly higher compared to GMFCS I-IV (6.4 %) and to the frequency of OSAS in typically developing (TD) children assessed by polysomnography (5.8 %) according to literature data. Significantly higher frequencies of palatine tonsil hypertrophy, hospitalizations and outpatient antibiotic use for respiratory causes (last 12 months), gastroesophageal reflux disease, drooling and epilepsy were found in GMFCS V. Palatine tonsil hypertrophy was significantly associated with HR-OSAS. GMFCS V was significantly correlated with HR-OSAS at the expense of its significantly higher prevalence of palatine tonsil hypertrophy. Conclusions: The prevalence of HR-OSAS in Brazilian children with CP (GMFCS V) was higher than the frequency of OSAS in TD children assessed by polysomnography. HR-OSAS was significantly more prevalent in GMFCS V compared with GMFCS I-IV. Palatine tonsil hypertrophy was significantly associated with HR-OSAS. GMFCS V was significantly correlated with HR-OSAS due to its significantly higher prevalence of palatine tonsil hypertrophy. PosaST may be a reliable questionnaire for Brazilian children with CP, but studies are needed to define the HR-OSAS cutoff score in this population.